Muzâra'ah As a Model and Practice of Pesantren Agricultural Cooperation in Improving the Welfare of Farmers in West Java - Aminulloh, Ali; Janwari, Yadi; Nurrohman, Nurrohman; Suntana, Ija (International Journal of Social Science, Education, Communication and Economics, 2024)
This research is motivated by the fact that there is still a lot of unproductive agricultural land in West Java, even though the agricultural sector contributes a lot to the community's economy. There needs to be an effort to involve various components of society, especially Islamic boarding schools, in increasing the productivity of agricultural land through cooperation using the muzâra'ah system involving many parties to improve the welfare of farmers and Islamic boarding schools. The aim of this research is to analyze and discover land management practices, cooperation models, and the impact of agricultural cooperation on the welfare of farmers in West Java. This research is field research using a qualitative approach. The research results show that, First, agricultural land management practices in West Java are collaborated with various parties, both internal Islamic boarding schools such as students, teachers and administrators as well as with the surrounding farming community. The two Islamic boarding school agricultural collaborations with the muzâra'ah system in West Java were expanded in scope, not just farmers and landowners, but there were elements of academics, government, the business world, financial institutions, markets and non-governmental organizations. Islamic boarding schools innovate agricultural cooperation with the quintuple helix model using multi contracts, namely connecting these parties to optimize the agricultural business being collaborated. Islamic boarding schools also build aspects of farmers' spirituality through guidance on the application of religious values in agricultural cooperation. Third, Islamic boarding school agricultural cooperation is able to absorb agricultural labor, so that farmers are able to improve their economy, have permanent jobs and increase their religious understanding and practice.